DAMPAK MEDIA PEMBELAJARAN TERHADAP NILAI BELAJAR PESERTA DIDIK KELAS 6 DI SD NEGERI LEDOK 06 SALATIGA - Shinta Herliana (LPPM Universitas Pahlawan Tuanku Tambusai, 2019)
The focus of this research is to investigate the impact of learning media towards the students’ value in grade six. This research was conducted in Ledok Elementary School State 6 in Salatiga by using survey with eighteen students as the number of the sample. Survey method was applied by the researcher in this research by giving questionnaire for students grade six. The result of this research showed that the use of learning media performed the strong impact towards the students’ learning achievement. In the development of elementary students, the students were in the a concrete operational phase. Moreover, the students need something real or all the learning process which involved the sensory in this phase. The use of learning media were effective to make the students became more enthusiastic and more active in the learning activity